Organic petrology of Ora formation in Akkas field, western Iraq - Mohamed W. Alkhafaji (Tikrit Journal of Pure Science, 2023)
Detailed petrological investigation of the organic matter has been performed using polished sections examined under incident light microscopy on the Lower Carboniferous Ora formation in Akkas field to characterize the nature and origin of the contained  organic matter in the shale beds. Microscopical investigations reveal that the organic matter consists of mixed terrestrial and marine organic matter. Marine organic matter represented by alginite and bituminte; whereas terrestrial is represented predominantly by sporinite, and minor amounts of vitrinite.